ASSERTIVE UTTERANCE USED IN READERSâ FORUM ON JAKARTA POST NEWSPAPER - Zulianti, Hajjah (STKIP Muhammadiyah Pringsewu, 2018)
This research aims to describe the forms, the types and the focus of assertive utterance used in readersâ forum on Jakarta post newspaper. This research is descriptive qualitative research. In collecting assertive utterances, the researcher uses observation method combined with noting technique. In analyzing the data, the researcher uses descriptive qualitative method. The result of analysis shows there are two forms of assertive namely direct and indirect assertive. The types of assertive are categorized into five; asserting, reporting, explaining, showing something, and suggesting. They focus on information, truth-value of utterance, speakerâs commitment in what is reported, and focus on aspect.